Teacher Educator Growth Across Rhizomatic Landscapes of Praxis - Gagné, Antoinette; Herath, Sreemali; Kalan, Amir; Ortega, Yecid; Rosado-Mendinueta, Nayibe (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
In this collaborative analytic autoethnography, five researchers and teacher educators from various contexts describe how their participation in a network of critical action researchers led to rhizomatic growth across their landscapes of praxis. Through the authors’ narratives, we learn how Deleuze and Guattari’s (1987) concept of the rhizome and Wenger’s (2015) notion of the landscape of practice are interconnected and have allowed multiple non-hierarchical points for engagement in research and knowledge mobilization. The autoethnography also illustrates how the outgrowth of a healthy rhizome can be more vibrant and lead to innovative approaches to education and research across various contexts.